Late Jurassic high-pressure metamorphism of Variscan I-Type granitoids in the Northern Part of the Pelagonian Unit (Republic of North Macedonia) - Altherr, Rainer; Hanel, Michael (Journal of petrology, 2024)
The high P/T metamorphic Pelagonian Unit in the Republic of North Macedonia comprises (1) a Variscan basement consisting of gneisses, schists and minor meta-mafic rocks, which are all intruded by I-type granitoids and rare related dikes; (2) a metamorphosed sedimentary sequence of Permian to Lower Triassic age, and (3) a sequence of calcite and dolomite marbles resulting from Late Triassic to Middle Jurassic carbonate sediments. All these rocks underwent a common high-P/T metamorphism of Late Jurassic age. This paper deals with the metamorphism of the Variscan I-type granitoids which contained the igneous mineral assemblage plagioclase I + alkali feldspar I + quartz I + biotite I + titanite I + allanite I + zircon I + apatite I ± magnetite I. During Late Jurassic high-P/T metamorphism, these undeformed granitoids were thoroughly metamorphosed under isotropic pressure conditions as documented by undeformed granitic textures that are overgrown by metamorphic minerals such as garnet II, epidote II, and phengite II. Various, eventually metasomatic mineral reactions took place in different textural positions: (1) Former igneous plagioclase grains became completely transformed to Na-rich plagioclase IIa (An09-14) containing numerous small grains of epidote IIa and phengite IIa. Either this transformation was an allochemical one and was accompanied by the syn-metamorphic introduction of an aqueous fluid phase containing Fe, Mg and K or, alternatively, the more Ca-rich parts of plagioclase I became considerably sericitized before high-P/T metamorphism, and the resulting mixture of more Na-rich relic plagioclase with its sericite-rich domains became later metamorphosed under high-P/T conditions. In the first case, an aqueous phase is needed during metamorphism, while in the second case high-P/T metamorphism might have proceeded under H2O-undersaturated conditions; (2) igneous alkali feldspar I was changed to albite-poor orthoclase II or microcline II; (3) igneous Ti-rich biotite I reacted with plagioclase to metamorphic garnet II + Ti-poorer biotite II + titanite II + phengite II + quartz II ± epidote II ± rutile II, which is rimmed by Ttn II. At textural positions, where igneous plagioclase I was not available, igneous biotite I was transformed to Ti-poorer biotite II + titanite II ± ilmenite-hematite II; (4) during uplift, high-P/T metamorphic rutile II became marginally overgrown by titanite II ± ilmenite II; (5) igneous allanite I grains stayed unaltered, but when located near to former plagiocase I, they became partially rimmed by metamorphic epidote II. Equilibrium phase diagram calculations showed that the observed metamorphic paragenesis (plagioclase II + K-rich feldspar II + biotite II + garnet II + epidote II + phengite II + garnet II + quartz II + rutile II + titanite II) is only stable under H2O-unsaturated conditions. The I-type granitoids and their metamorphic country rocks were metamorphosed under high-P/T conditions of 1.3 to 1.5 GPa and 560 to 590 °C.
Gesehen am 10.04.2025